O101 Increased contractile activity through electrical stimulation attenuates postoperative loss of muscle mass and function, even in the presence of inadequate nutrition. (22nd July 2022) - Hardy, E; Hatt, J; Doleman, B; Smart, T; Phillips, B; Lund, J
Abstract: Introduction: Significant muscle atrophy occurs after major abdominal surgery. Lack of physical activity and protein intake may play a significant role. This study assesses the efficacy of neuromuscular electrical stimulation (NMES) in attenuating loss of muscle mass and function following open colorectal resection. Methods: Fifteen patients were recruited, and their lower limbs randomised to control (CON) or NMES (STIM). Vastus Lateralis (VL) cross sectional area (CSA), muscle thickness (MT) and knee extensor strength (KES) were measured preoperatively and repeated on postoperative day (POD) 5. Dietary intake was recorded, and nutritional intake calculated. Fifteen minutes of NMES was applied to the quadriceps of the STIM leg twice a day on POD 1–4. All outcomes were analysed using linear mixed model approaches. The study was approved by the NHS REC (ref 20/EM/069). Results: NMES significantly reduced the loss of CSA (mean difference (MD) 1.18, 95%CI: 0.75–1.61, p<0.001), MT (MD 0.12, 95%CI: 0.04–0.2, p=0.001) and KES (MD 4.48, 95%CI: 0.00–8.97, p=0.03). Total energy and protein intakes over POD1 - 4 were 42.6% (± 19.7) and 21.1% (± 11.4) of the ESPEN recommended daily amount for perioperative patients. No adverse events occurred, and patients reported that NMES caused minimal or no discomfort. Conclusion: NMES has been demonstrated to reduce loss of muscle mass and function following major abdominal surgery and may be an important tool in aiding recovery to normal functional state. Further studies should establish the efficacy of bilateral whole-leg NMES for improving patient centred outcomes. Take-home message: Loss of muscle mass and function after major abdominal surgery causes significant morbidity. Neuromuscular electrical stimulation reduces this muscle loss and should be investigated further as a potential therapy.